Performance of Nurses in Neonatal Intensive Care Unit Regarding Transfusion of Blood and Blood Products - Samane Sefatbaqa; Seyedeh Roqayeh JafarianAmiri; Ali Zabihi; Parisa Pourdad; Afsaneh Arzani (Mashhad University of Medical Sciences, 2020)
Background: Critically ill neonates receiving blood products are at risk of transfusion-related complications. The quality of nursing care in this regard can be enhanced through continuous evaluations. Aim: This study aimed to assess the performance of nurses in a neonatal intensive care unit (NICU) regarding the transfusion of blood and blood products. Method: This descriptive cross-sectional study was carried out on the nurses working in an NICU in Tehran, Iran, during 2017. The performance of nurses was investigated for 550 blood transfusion procedures by structured observation through a researcher-made checklist with 40 items in three steps. The data were analyzed using SPSS software (version 22) using descriptive statistics and a generalized estimating equation. Results: The highest frequency (66.2%; n=365) of transfusions was observed for fresh frozen plasma. In the pre-transfusion phase, no case out of 550 transfusion procedures, ensuring the openness of the vein with normal saline injections run (100%), the carriage of blood products from the blood bank to the ward by the box Specific (76.2%), assess blood and blood products sensitivity (34.1%) and control of blood tests for blood count and coagulation factors (20.5%). In the transfusion phase, slow shaking the blood bag during injection (68.6%) and venous line washing with saline solution (45%) were not according to guidelines. After the transfusion phase, the volume of infused products, blood types, post-transfusion reactions and vital signs, and status of product labeling were recorded in 100% of the nursing reports. Implications for Practice: The performance of nurses was poor in many cases during the transfusion stage which can affect the health of the neonates. Therefore, it is recommended to provide continuous and persistent training for the staff.